Investigations on an advanced power system based on a high temperature polymer electrolyte membrane fuel cell and an organic Rankine cycle for heating and power production. (August 2015) - Perna, Alessandra; Minutillo, Mariagiovanna; Jannelli, Elio
Abstract: Energy systems based on fuel cells technology can have a strategic role in the range of small-size power generation for the sustainable energy development. In order to enhance their performance, it is possible to recover the " waste heat " from the fuel cells, for producing or thermal power (cogeneration systems) or further electric power by means of a bottoming power cycle (combined systems). In this work an advanced system based on the integration between a HT-PEMFC (high temperature polymer electrolyte membrane fuel cell) power unit and an ORC (organic Rankine cycle) plant, has been proposed and analysed as suitable energy power plant for supplying electric and thermal energies to a stand-alone residential utility. The system can operate both as cogeneration system, in which the electric and thermal loads are satisfied by the HT-PEMFC power unit and as electric generation system, in which the low temperature heat recovered from the fuel cells is used as energy source in the ORC plant for increasing the electric power production. A numerical model, able to characterize the behavior and to predict the performance of the HT-PEMFC/ORC system under different working conditions, has been developed by using the AspenPlus™ code. Highlights: The advanced plant can operate both as CHP system and as electric generation system. The performance prediction of the integrated system is carried out by numerical modeling. ORC thermodynamic optimization is carried out by a sensitivity analysis. Thermal coupling between the HT-PEMC system and the ORC plant is analyzed. Results are very promising in the field of the distributed generation.